The level of environmental awareness of the phenomenon of environmental pollution among teachers of social studies in the light of some variables - Al- alawi, Salma Ali Humaid; Al- mamari, Saif Nasser Ali (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the level of environmental awareness of the phenomenon of environmental pollution among teachers of social studies in the Sultanate of Oman in the light of some variables, in addition to determining the impact of variable academic qualification and years of teaching experience. It was verified that it was (0.88). The study sample consisted of 28 teachers of social studies for the second cycle. The study sample consisted of 28 teachers of social studies for the second cycle. The most prominent results were: The level of environmental awareness of the phenomenon of environmental pollution among teachers of social studies was very high. The average sample responses ranged between (4.2- 4.7). The level of environmental awareness of the phenomenon of environmental pollution does not vary according to academic qualification and the number of years of experience. In the light of the results of the study, the researchers recommend the preparation of programs and training courses for teachers of social studies to prepare them environmentally, and acquire environmental concepts and knowledge, and familiarize them with environmental problems and how to address them and the optimal exploitation of environmental resources, and not limited to the verbal side in those programs and courses, and attention to the teacher in the academic preparation phase of During his teaching courses related to the environment.